The Effect Of Good Corporate Governance On Capital Structure With Profitability As An Intervening Variable In The Transportation Sector Listed On The IDX (2019-2022) - Sairi, Talitha Daffa; Athori, Agus (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This research aims to analyze the influence of good corporate governance on capital structure with profitability as an intervening variable in the transportation sector listed on the IDX (2019-2022). The Good Corporate Governance variable is proxied by the Board of Commissioners, Capital Structure is proxied by the Debt to Asset Ratio (DAR), Profitability is proxied by Return On Assets (ROA). The sampling technique in this research used the purposive sampling method. The number of samples in this research was 19 companies. This research is quantitative research using Path Analysis and Sobel test. The research results show that Good Corporate Governance (Board of Commissioners), Profitability does not have a significant effect on Capital Structure (DAR), Good Corporate Governance (Board of Commissioners) does not have a significant effect on Profitability (ROA), Profitability (ROA) is not able to mediate the relationship between Good Corporate Governance (Board of Commissioners) with Capital Structure (DAR).